Selective bond scission in formic acid by low-energy electrons. Issue 5 (January 2020) - Griffin, Brandon; Moradmand, Ali; Williams, Joshua; Belkacem, Ali; Rescigno, Thomas N; Trevisan, Cynthia; McCurdy, C William; Weber, Thorsten; Slaughter, Daniel S
Abstract: We report recent results of mass-resolved anion fragment momentum imaging experiments to investigate dissociative electron attachment to formic acid, for incident energies between 5 eV and 9 eV. A remarkable site-selectivity is found for a resonance at 8.5 eV by comparing anion fragment yields for two deuterated isotopologues of formic acid. This results in an H − fragment from the O-H bond of the transient anion, with negligible contribution from C-H break. In contrast, a lower-energy resonance at 7.1 eV dissociates by C–H or O–H break to produce H − and the neutral radicals HOCO or HCOO.